Senyawa flavonoid kurma ajwa (Phoenix dactylifera L.) sebagai terapi kanker: Efektivitas flavonoid kurma ajwa sebagai penghambat jalur PI3K/Akt pada gen anti-apoptosis (bcl-2) pada kanker payudara - Fuadati, Ifrokhatul (Maliki Interdisciplinary Journal, 2026)
Breast cancer is one of the leading degenerative diseases causing high mortality among women worldwide. The development of cancer is associated with uncontrolled cell proliferation and the failure of apoptosis mechanisms, which is influenced by increased expression of anti-apoptotic genes such as BCL-2. One factor that contributes to this process is the presence of reactive oxygen species (ROS) that activate the PI3K/Akt signaling pathway and the transcription factor NF-κB. Ajwa date (Phoenix dactylifera L.) contains phytochemical compounds, particularly flavonoids, which exhibit strong antioxidant activity. This article aims to examine the potential of flavonoids from Ajwa dates as a natural therapy for breast cancer through the inhibition of the PI3K/Akt signaling pathway. Flavonoids neutralize ROS and inhibit PI3K activation, preventing Akt activation. This condition suppresses NF-κB activation that regulates BCL-2 expression. Consequently, the inhibition of this pathway reduces anti-apoptotic gene expression and promotes apoptosis in cancer cells. Therefore, Ajwa date flavonoids have potential as a targeted natural therapy for breast cancer treatment.